Global Muslims in the age of steam and print - Gelvin, James L., 1951-; Green, Nile. (Berkeley : University of California Press, 2014)
"The second half of the nineteenth century marks a watershed in human history. Railroads linked remote hinterlands with cities; overland and undersea cables connected distant continents. New and accessible print technologies made the wide dissemination of ideas possible; oceangoing steamers carried goods to distant markets and enabled the greatest long-distance migrations in recorded history. In this volume, leading scholars of the Islamic world recount the enduring consequences these technological, economic, social, and cultural revolutions had on Muslim communities from North Africa to South Asia, the Indian Ocean and China. Drawing from a multiplicity of approaches and genres, from commodity history to biography and social network theory, the essays in Global Muslims in the Age of Steam and Print, 1850-1930 offer new and diverse perspectives on a transnational community in an era of global transformation. "--
"The second half of the nineteenth century marks a watershed in human history. Railroads linked remote hinterlands with cities; overland and undersea cables connected distant continents. New and accessible print technologies made the wide dissemination of ideas possible; oceangoing steamers carried goods to distant markets and enabled the greatest long-distance migrations in recorded history. In this volume, leading scholars of the Islamic world recount the enduring consequences these technological, economic, social, and cultural revolutions had on Muslim communities from North Africa to South Asia, the Indian Ocean and China. Drawing from a multiplicity of approaches and genres, from commodity history to biography and social network theory, the essays in Global Muslims in the Age of Steam and Print offer new and diverse perspectives on a transnational community in an era of global transformation"--
Includes bibliographical references and index.
Keywords: Islamic civilization -- 19th century; Technology -- Islamic countries -- History -- 19th century; Islamic countries -- History -- 19th century